Preliminary study on the development and storage stability of carrot ice cream - Canja, Vivien Mae J. (2001.)
Carrot ice cream formulations with 20%, 40%, and 60% carrot puree were prepared and subjected to preference test.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Carrot ice cream